Maternal Latent Mycobacterium tuberculosis Does Not Affect the Infant Immune Response Following BCG at Birth: An Observational Longitudinal Study in Uganda - Lubyayi, Lawrence; Mawa, Patrice A.; Nabakooza, Grace; Nakibuule, Marjorie; Tushabe, John Vianney; Serubanja, Joel; Aibo, Dorothy; Akurut, Hellen; Tumusiime, Josephine; Hasso-Agopsowicz, Mateusz; Kaleebu, Pontiano; Levin, Jonathan; et al. (Frontiers in Immunology, 2020)
Background: BCG has low efficacy in tropical countries. We hypothesised that maternal latent Mycobacterium tuberculosis (M.tb) infection (LTBI) results in fetal tolerance to mycobacterial antigens and impaired responses to BCG immunisation. Methods: We enrolled 132 LTBI-positive and 150 LTBI-negative mothers and their babies in Entebbe, Uganda. Infants were BCG-immunised at birth. Cord blood and samples at weeks 1, 4, 6, 10, 14, 24 & 52 were analysed for cytokine/chemokine responses to M.tb antigens by Luminex 17-plex assay in 6-day whole blood cultures and antibody responses by ELISA. Of the 17 Luminex analytes, seven (IL-2, IL-5, IL-10, IL-13, IL-17A, TNF, and IFN-gamma) were included in the main analysis as they were considered most likely to represent T cell responses. Immune sensitisation was defined as a detectable cord blood cytokine response to PPD for any of the seven cytokines. Patterns of cytokine and antibody responses were compared between infants of mothers with and without LTBI using linear mixed models adjusting for confounders. Results: Most infants (73%) were sensitised in utero to M.tb antigens, with no overall difference seen between infants born to mothers with or without LTBI. Patterns of post-BCG cytokine and antibody responses to mycobacterial antigens were similar between the two infant groups. Conclusions: Our data do not support the hypothesis that maternal LTBI results in an impaired response to BCG immunisation, in Ugandan infants. BCG vaccination at or shortly after birth is likely to be beneficial to all infants, irrespective of maternal LTBI status.